FORMATION OF HYDROPHILIC VEGETATION IN SOME RESERVOIRS OF THE SOUTHERN ARAL SEA REGION - Bektursinov, Askar Bekbauliyevich (SCIENCE and SOCIETY, 2026)
Research was conducted in some reservoirs of the Southern Aral Sea region (Muynak Bay, Sarbas, Shegekul, Koksu) to study the formation of hydrophilic vegetation and the dynamics of higher aquatic vegetation under conditions of unstable hydrological regime during the 2009-2024 period. The vegetation of water bodies was investigated under conditions of unstable hydrological regime.
Keywords: Southern Aral Sea region; Muynak Bay; Sarbas; Shegekul; hydroregime; higher aquatic vegetation; water milfoil; pondweed